AN INVESTIGATION OF INDONESIAN EFL TEACHERSâ PERCEPTION OF COMMUNICATIVE LANGUAGE TEACHING - Daflizar, Daflizar (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2013)
Over the past three decades, the Communicative Language Teaching (CLT) has become one of the most dominant approaches in the field of ESL or EFL teaching in many countries around the world, including Indonesia. The aims of this study were threefold: (a) to investigate Indonesian EFL teachersâ theoretical perceptions of CLT, (b) to look at whether the teachers have implemented CLT in the classroom, and (c) to identify difficulties the teachers face in implementing CLT. The participants in the study were 7 Indonesian EFL teachers who were pursuing their study in TESOL and Foreign Language Teaching program at the University of Canberra. Thirty-item questionnaires were used for data collection. The results of the study revealed that the teachers involved in this study generally had considerably good understanding of principles and activities of CLT. Most of the teachers also reported thatthey have implemented CLT in their classrooms even though many of them still maintained activities of traditional approaches. The results also revealed that all of the teachers face some constraints in implementing CLT activities in their classrooms. Among the most common constraints include low English proficiency of the students, large classrooms, and lack of sources.Â Â